Adrenoleukodystrophy: Symptoms, Treatment and Newborn Screening. Literature Review and Clinical Case - Laura Regelskytė; Rūta Praninskienė (Neurologijos seminarai)
Adrenoleukodystrophy is a rare genetic disease which causes adrenal gland insufficiency and damages the nervous system. It is inherited through the X chromosome in a recessive manner. Due to the ABCD1 gene mutation, there is a disorder of peroxisomes, thus very long-chain fatty acids are not degraded properly. There are 3 main forms of X-ALD: cerebral X-adrenoleukodystrophy, adrenomyeloneuropathy, and Addison’s disease. We present a case of a 7-year-3-month-old boy who was diagnosed with cerebral X-adrenoleukodystrophy. The patient was hospitalised because of episodic strabismus, hearing difficulty, gait abnormalities, and behavioural changes. His maternal grandmother had an unspecific demyelination. There were typical lesions of X-adrenoleukodystrophy in the patient’s magnetic resonance tomography imaging, whereas the Loes score was 15. Laboratory testing showed an elevated concentration of very long-chain fatty acids, and genetic testing confirmed the ABCD1 gene mutation. The patient’s disease was evaluated as advanced; therefore, allogeneic stem cell transplantation was not performed. The treatment consisted of Lorenzo oil, hormone therapy, and a low-fat diet. After summarising the literature, 6 main groups of symptoms are suggested: behavioural changes, hearing and visual impairment, neuromuscular system disorders, central nervous system impairment, nonspecific and other non-neurological symptoms. The best results of allogeneic stem cell transplantation were observed in patients with standard or very low risk. Autologous stem cell transplantation with gene therapy showed similar results as allogeneic stem cell transplantation. Vorinostat, rituximab, and intrathecal mesenchymal stem cell transplantation were described as unsuccessful treatment methods. The prevalence of X-ALD is estimated from 1:4,845 to 1:17,000, depending on the country. The most effective value of C26:0 Lyso-phosphatidylcholine concentration for newborn screening was 0.3-0.36 μmol/l.